BIOLOGY OF THE LARGE-SCALED TONGUE SOLE CYNOGLOSSUS MACROLEPIDOTUS (BLEEKER) - Ramanathan, N; Vijaya, P; Ramaiyan, V; Natarajan, R (Indian Journal of Fisheries, 2011)
The biometry of C. macrolepidotus us&ng the regression equ~tion y = a + bxhas lnen stllidi1ed; the regression Hnes based on the angle of